Texas community college faculty attitudes and perceptions about professional development - Hyak, Sharon Kay Geistman (Kansas State University, 2020)
As community colleges focus on increasing accountability, a growing number of community colleges have implemented professional development programs. Studies have demonstrated the effectiveness of faculty professional development, yet faculty participation and attitude toward training may impede improvement efforts. Therefore, the purpose of this quantitative study was to increase understanding of Texas community college faculty attitudes and perceptions about faculty (teacher training) professional development. This quantitative study identified faculty characteristics, such as teaching experience, level of teacher training received, and academic degree earned; as well as environmental factors including college culture, administrative support, colleague influence, funding, time availability, self-efficacy and faculty perceptions toward development activities. A Likert-style online survey was developed and administered at 14 Texas community campuses, where 997 faculty members participated. The faculty list included campus members that taught at least one course in a typical semester, including teaching administrators, deans, part-time faculty, and full-time faculty. The Likert items mostly consisted of five points based on the scales from “Strongly Disagree” to “Strongly Agree,” or from “Never” to “Very Frequently.” Other questions established participation in faculty development activities and demographic information such as teaching load, prior teacher training, academic degree earned, teaching discipline, teaching experience, and position at the college. Survey data were analyzed using Excel and SPSS statistical software. One-way Analysis of Variance (ANOVA) and multiple regressions was performed to determine the relationship among survey variables. A priori level of significance for all statistical analyses was set at an alpha level of 0.05. Participants included 997 Texas community college faculty members at 14 campuses. Results indicated that (a) differences exist in the ways these various faculty groups experience and value training opportunities; (b) campus culture, administrative support, and funding, are statistically significant predictors of faculty member participation, attitudes, and perceptions; (c) faculty members’ self-efficacy is significant in predicting attitudes about professional development; and (d) faculty beliefs in their teaching capacity influence their motivation and behavior in the classroom. The researcher recommends that leadership (a) legitimize professional development by promoting, supporting, and participating in strategically aligned programs; (b) evolve training strategies to incorporate diverse objectives, learning strategies, and shared culture for all generations and experience levels; (c) present training using best practices, reflection, and a comprehensive approach; and (d) model high-achieving systems of education. Several recommendations for future research include (a) continually and consistently collect and analyze data regarding faculty attitudes and faculty experiences; (b) evaluate how faculty development training affects student learning; (c) expand research to systems of education that reflect high-achieving models and alignment with the desired culture and strategic directions.
Keywords: Community college faculty; Professional development; Faculty attitudes; Campus culture